INCORPORATING SYSTEM DYNAMICS INTO WORK ERGONOMIC ANALYSIS: A CASE STUDY IN THE FOOTWEAR INDUSTRY (Human Factors in Design, 2025)
Ergonomic analyses require a broader understanding of the interplay between various factors to ensure more efficient diagnostics. This study aimed to develop a Work Ergonomic Analysis (WEA) and, from there, to construct a Causal Loop Diagram (CLD) to examine the working conditions in the footwear industry. The methodology was based on the stages of WEA and subsequently integrated the CLD. Five loops (closed cycles of cause and effect) were identified, with two being particularly significant: the Influence of Workload on Physical Overload and the Influence of Movements on Physical Recovery. It was concluded that integrating the CLD enhanced the analytical capacity and provided more informational support for optimizing the identified conditions.